2002
DOI: 10.1091/mbc.02-05-0083
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Recruitment of Fibrillarin to Nucleoplasmic Proteasomes: Implications for Processing of a Nucleolar Autoantigen

Abstract: A prerequisite for proteins to interact in a cell is that they are present in the same intracellular compartment. Although it is generally accepted that proteasomes occur in both, the cytoplasm and the nucleus, research has been focusing on cytoplasmic protein breakdown and antigen processing, respectively. Thus, little is known on the functional organization of the proteasome in the nucleus. Here we report that within the nucleus 20S and 26S proteasomes occur throughout the nucleoplasm and partially colocaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
1
3

Year Published

2005
2005
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 58 publications
7
59
1
3
Order By: Relevance
“…Alterations in the molecular context of cryptic nuclear proteins by environmental factors might lead to efficient processing and presentation of the proteins (16,17). Results from other studies and our previous investigations in cell culture and animal models have shown that xenobiotics, such as heavy metals, drugs, and viruses, recruit SSc autoantigens for antigen processing via proteasomes (18,19). Based on these results, we propose the following hypothesis for the generation of systemic autoimmune responses.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Alterations in the molecular context of cryptic nuclear proteins by environmental factors might lead to efficient processing and presentation of the proteins (16,17). Results from other studies and our previous investigations in cell culture and animal models have shown that xenobiotics, such as heavy metals, drugs, and viruses, recruit SSc autoantigens for antigen processing via proteasomes (18,19). Based on these results, we propose the following hypothesis for the generation of systemic autoimmune responses.…”
mentioning
confidence: 70%
“…Recently we showed that xenobiotics such as heavy metals induce redistribution and colocalization of fibrillarin in cell culture and in animal models (18). Although ANAs to fibrillarin are specific for SSc, their frequency is rather low (3-8%) (24).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations